The rights and obligation free lecturer - عبد القادر بان صلاح; نوري امير عماد (Journal of Legal Sciences, 2021)
Among the duties of the state is to organize the lives of individuals in all respects, and among the categories that the state has to organize their lives are the category of new graduates who are looking for work, As a result of the conditions that accompany our dear country, such as the deterioration of economic life, the rise in unemployment, the inability of the state to recruit graduates as a whole, and the shortage that has appeared in the teaching staff in schools, especially those located in remote areas of the governorates, Studies have shown that there is a significant shortage of teaching staff, which prompted the state to create a new category, the category of free lecturers, and they are people who pledge to give free lectures in Iraqi schools, provided that they have priority when opening new appointments. This case, despite helping it complete the teaching quorum and helping it fill the shortage in schools, this system has many negatives and many problems that have appeared and may appear in the future, including the legal status of these people and what their rights and obligations are, and this is what we have tried to address through this research.